Labor market spillover effects of a compulsory schooling reform in Germany - Schiele, Valentin
Compulsory schooling reforms are often used to estimate monetary returns to education. Such reforms are unrelated to individual characteristics and preferences and thus arguably able to eliminate selection bias. However, as these reforms affect a large number of individuals in the relevant age groups, they might have spillover effects on individuals not directly affected by the reform. Such spillover effects constitute a problem for identification and estimation of returns to schooling. As they are difficult to address, they are mostly ignored in the empirical literature. I show that the introduction of the compulsory ninth grade in Germany led to a labor supply shock that might have increased wages and employment of individuals who were not directly subject to the reform and were assumed not to be affected in previous research. To investigate in this kinds of spillover effects, I exploit the staggered introduction of the compulsory ninth grade across German federal states in a difference-in-differences approach. Based on large scale register and survey data, I find no evidence for persistent spillover effects for men. For women, however, my results suggest that the labor supply shock resulting from the reform may have led to a persistent increase in employment and wages.
Keywords: Compulsory schooling; Education; Spillover effects; Cohort size; Wages; Employment

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program